THE FREQUENCY OF HYPOTHERMIA IN LAPAROSCOPIC PARTIAL GASTRECTOMY AT CHO RAY HOSPITAL, YEAR 2021 (Vietnam Journal of Community Medicine, 2021)
Introduction: Currently, the hypothermia in laparoscopic gastrectomy has not been given due attention, leading to a high rate of postoperative hypothermia. Therefore, the care, monitoring and intervention to reduce the rate of hypothermia during and after surgery is one of the issues that need attention.Objectives: The study was carried out with 2 objectives: (1) Determining the rate of hypothermia in patients during laparoscopic partial gastrectomy at Cho Ray Hospital; (2) Understanding risk factors for hypothermia in laparoscopic partial gastrectomy patients.Methods: Descriptive cross-sectional study on 65 laparoscopic partial gastrectomy patients under general endotracheal anesthesia, from February 2021 to July 2021. The temperature was continuously measured and noted every 30 minutes from induction to the end of surgery by esophageal probe.Results: In the study, all patients were under endotracheal anesthesia, The proportion of the age group 70 years and older is 35.38%, the rate of male 76.92%. The average anesthetic time was 166,77±44,05 minutes, the mean surgery time was 145,0±42,70 minutes. The average temperature of the operating room is 23,79°C. The rate of 87,69% of patients was warmed with just a sheet. Research results show that the rate of hypothermia in patients after surgery is 72,31%. Factors related to the rate of hypothermia include age group over 70, smoking, method of warming, BMI, operating room temperature.Conclusion: Need to monitor the body-temperature and use continously  critacal warming methods the prevent the hypothermia during and after gastrectomy surgery patients.
Keywords: Hypothermia, laparoscopic partial gastrectomy, risk factors, Cho Ray Hospital.